Nitrogen uptake and expression of nitrogen transporters of selected upland rice - Mohd Amin, Adibah (2016)
Nitrogen (N) is one of the most yield limiting nutrients for upland rice production. The differences in N accumulation in plants have been attributed to the N uptake ability of the roots. The most important aspect of this research is to determine potential factors that can contribute to nitrogen use efficiency (NUE). The objectives of this study are: 1) to determine the NUE of selected upland rice landraces. 2) to determine the root characteristics of upland rice as influenced by nitrogen fertilization, and 3) to identify the expression of high-affinity ammonium transporter that is expressed under different nitrogen level. The first study was focused on NUE of selected upland rice landraces as affected by P fertilization. Five landraces of upland rice seedlings were transplanted in plots treated with two P levels (0kg P/ha and 100kg P/ha). The 15N source is from 15N labelled ammonium sulphate fertilizer [15(NH4)2SO4] with 1% 15N atom excess. The %N derived from fertilizer (%Ndff) was calculated using the equation based on isotope dilution technique. The performance of the landraces in taking up the N fertilizer was evaluated by comparing the NUE. At 4 and 8 weeks after transplanting, the NUE had no significant differences between the landraces (p ≥ 0.05). However, Landrace I had the highest NUE during 8 weeks after transplanting which was 33.59% higher as compared to other landraces. At week 16 after transplanting, the landraces that showed significant effects on NUE (p ≤ 0.05) was Landrace III with the highest NUE which was 52.59% more than landrace I which had 27.50%. The P fertilization had no significant effects on NUE, dry matter yield and grain yield at week 4, 8 and 16 of all the selected upland rice landraces. The second experiment on root characterization of five upland landraces was planted at Field 10, UPM. Six treatments were applied: (1) 150kg/ha N as Ammonium sulphate (2) 75 kg/ha N as Ammonium sulphate (3) 150kg/ha N as Potassium nitrate (4) 75 kg/ha N as Potassium nitrate (5) Control (0kg/ha N) of Ammonium sulphate (6) Control (0kg/ha N) of Potassium nitrate. The root parameters were recorded since root surface area is important for nutrient uptake. Landrace III had the highest total surface area at both low and high N rates at week 12 and had resulted in high NUE of the landrace. There were significantly positive correlations between bleeding rate and root surface area. The third experiment on the expression of high-affinity ammonium transporter was carried on two upland rice landraces that showed high NUE and low NUE. They were chosen from a previous field experiment. Plants were treated with modified Yoshida nutrient solution with 0.05mM NH4NO3, 0.1mM NH4NO3, 1mM NH4NO3 and 2mM NH4NO3. The expression of ammonium transporter (OsAMT1;1) was determined. Landrace III had the highest expression of the transporter compare to Landrace I, thus supporting the results that landrace III had significantly higher NUE compared to Landrace I.